INTERMITTENT IRRIGATION AND CUTTING HEIGHT ON RATOON RICE (Oryza sativa L.) - Setiawan, Adi; Tyasmoro, Setyono Yudo; Nugroho, Agung (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2014)
The purpose of this study was to examine the methods of intermittent irrigation and cutting height on growth and yield of ratoon rice (Oryza sativa L.). The research was conducted on alluvial soil in Malang, ca. 507 m above sea level (asl), by using split plot design. The main plot was without flooding interval of rice field i.e.0 (full flooding), 2, 4 and 6 days. The sub plot was ratoon height i.e. 0-5 cm, 10-15 cm and 20-25 cm. The result showed that there was no significant interaction between without flooding intervals and cutting height. The result of grilled dry spikelet weight of the first crop was 5.78 t ha-1.The result of second crop showed that the treatment of 0 day (full flooding) gave the highest yield (3.12 t ha-1), decreased of 46% from the first crop.The rice crop which was ratooned of 0-5 cm in height resulted the highest yield (2.95 t ha-1), decreased of 49% from the first crop.Keywords: intermittent irrigation, rice (Oryza sativa L.), ratoon, flooding